(untitled) (Semiárida, 2020)
The present study was carried out in order to estimate the quality of the cumulative growth in annual white sweet clover (Melilotus alba Medikus), its component fractions, and its variations over time. Evaluation started when the planta reached 16.5 cm in height (vegetative stage) and continued up to the fructification stage. Eight treatments (sampling dates) were arranged in a randomized complete block design with three replications. Total removal of forage was done at each sampling date. Crude protein % (CP %), neutral detergent fiber % (NOF %), and dry matter in situ digestibility % (OMISO %) of leaf and stem fractions and whole plant were estimated. Mathematical models representing the relationships between the independent variable "number of days from thirst cut" and the dependent variables CP %, NOF %, and OMISO % were developed. In each case the correspondent R’ was calculated. Leat %, CP % and NOF % were used to predict whole plant OMISO %. High forage quality was maintained until flowering initiation. After this 5tage was reached, quality decreased with the advance of maturity mainly because of the decrease in leaf %. We conclude that annual white sweetclover should not be utilized after flowering to obtain high quality forage.